Skin Manifestations of Inflammatory Bowel Disease - Huang, Brian L.; Chandra, Stephanie; Shih, David Q. (Frontiers in Physiology, 2012)
Inflammatory bowel disease (IBD) is a disease that affects the intestinal tract via an inflammatory process. Patients who suffer from IBD often have diseases that affect multiple other organ systems as well. These are called extraintestinal manifestations (EIMs) and can be just as, if not more, debilitating than the intestinal inflammation itself. The skin is one of the most commonly affected organ system in patients who suffer from IBD. The scientific literature suggests that a disturbance of the equilibrium between host defense and tolerance, and subsequent over-activity of certain immune pathways, are responsible for the cutaneous disorders seen so frequently in IBD patients. The purpose of this review article is to give an overview of the types of skin diseases that are typically seen with IBD and their respective pathogenesis, proposed mechanisms, and treatments. These cutaneous disorders can manifest as a metastatic lesion, reactive process to the intestinal inflammation, association by genetic linkage and autoimmune processes, complication of IBD itself, as side effects from IBD treatments, and from other mechanisms that will be discussed in this article. Ultimately, it is important for healthcare providers to understand that skin manifestations should always be checked and evaluated for in patients with IBD.